Are Meteorological Factors, Seasons, and Time of Onset Associated With Acute Scrotum? A Comparative Study of Testicular Torsion and Torsion of the Appendix Testis or Epididymis - Harada, Junki; Mitsunari, Kensuke; Fukushima, Hajime; Kurata, Hiroki; Nakamura, Yuichiro; Matsuo, Tomohiro; Ohba, Kojiro; Mochizuki, Yasushi; Imamura, Ryoichi (Sage Open Pediatrics, 2025)
Testicular torsion (TT) and torsion of the appendix testis or epididymis (TATE) are common causes of the acute scrotum, but differentiating them remains difficult. While meteorological factors have been linked to TT, their clinical significance is unclear. We retrospectively analyzed TT and TATE cases diagnosed via surgical exploration at Nagasaki university hospital (June 2018-March 2023). Clinical findings, seasonal variations, and meteorological factors-including temperature, atmospheric pressure, and humidity-were evaluated. Among 53 cases (31 TT, 22 TATE), TT patients were significantly older (median: 14.0 years, = 0.026) and more frequent in winter ( = 0.023). TT onset correlated with lower maximum, minimum, and ambient temperatures ( = 0.010, 0.024, 0.006). Over 90% of cases between midnight and 8:00 am were TT. TT is associated with lower temperatures, winter, and midnight to morning onset. These findings may enhance diagnostic accuracy and clinical decision-making.